(untitled) (Revista Apotheke, 2021)
Alinhavadas is a poetic experience in which I invite friends, students or interested parties to sew skirts through self-modelling, using only the basting stitch. In 2019, I sewed with small groups, talking about the possible meanings and visualities that we could build: what does the use of this textile artifact say about our historical-cultural moment? What can I learn and create from other people’s narratives about wearing skirts? What can we learn from these memories that leave clothes as legacies? In the face of actions to fight the COVID19 pandemic, the tacking of the skirt became a pretext for the generation of virtual or individual meetings. Alinhavadas is part of the a/r/tographic research Textile Narratives and Artist Teaching, in the field of Visual Culture Education, under contributions by John Dewey (2010).